ANALYSIS THE IMAGERY OF FATHER IN SYLVIA PLATH’S POEMS : ‘DADDY’ & ‘THE COLOSSUS’ - Mita Permata Sari; Nurul Wahidah; Anisa Nur’Aini (Yayasan Nusantara Hasana Berdikari, 2024)
This research analyzes the use of father imagery in Sylvia Plath's poems